Association of cardiovascular risk factors with the different presentations of acute coronary syndrome - Evelise Helena Fadini Reis Brunori; Camila Takáo Lopes; Agueda Maria Ruiz Zimmer Cavalcante; Vinicius Batista Santos; Juliana de Lima Lopes; Alba Lucia Bottura Leite de Barros (Universidade de São Paulo, 2014)
OBJECTIVE: to identify the relationship between different presentations of acute coronary syndrome and cardiovascular risk factors among hospitalized individuals.METHOD: cross-sectional study performed in a teaching hospital in São Paulo, in the State of São Paulo (SP). Socio-demographic, clinical and anthropometric data of 150 individuals hospitalized due to acute coronary syndrome were collected through interviews and review of clinical charts. Association between these data and the presentation of the syndrome were investigated.RESULTS: there was a predominance of ST segment elevation acute myocardial infarction. There was significant association of systemic hypertension with unstable angina and high values of low density lipoprotein with infarction, without influence from socio-demographic characteristics.CONCLUSION: arterial hypertension and high levels of low-density lipoprotein were associated with different presentations of coronary syndrome. The results can provide support for health professionals for secondary prevention programs aimed at behavioural changing.